Oleanolic acid enhances neural stem cell migration, proliferation, and differentiation in vitro by inhibiting GSK3β activity. Issue 1 (December 2018) - Zhang, Shi; Lin, Kai; Law, Cheuk; Liu, Bin; Fu, Xiu; Tse, Wing; Wong, Samantha; Sze, Stephen; Yung, Ken
Abstract Oleanolic acid (OA), one of the bioactive ingredients in ginseng, has been reported to have neuroprotective activities. However, the effects and its mechanism on neural stem cell (NSC) induction are not entirely clear. In the present study, we investigated the effects of OA on promoting the migration, proliferation, and differentiation of neural stem cells (NSCs). Migration and proliferation were investigated by using neural-specific markers, neurosphere assay, and Cell Counting Kit-8, respectively. We found OA remarkably promoted neural migration and proliferation of NSCs in a time- and dose-dependent manner. Differentiation was analyzed by western blotting and immunofluorescence staining, which found MAP2 expression was remarkably increased, whereas Nestin was dramatically decreased. In addition, OA increased phosphorylation of GSK3β at Ser9 and expression of active forms of β-catenin. Furthermore, NSCs with constitutively active GSK3β (S9A) significantly suppressed the OA-induced proliferation and neural differentiation. These results showed that OA could stimulate NSC proliferation and neural differentiation in vitro via suppressing the activity of GSK3β. Our findings may have significant implications for the treatment of neurodegenerative diseases.